2015
DOI: 10.1371/journal.pone.0143348
|View full text |Cite
|
Sign up to set email alerts
|

Association of Erythropoietin-Stimulating Agent Responsiveness with Mortality in Hemodialysis and Peritoneal Dialysis Patients

Abstract: Erythropoiesis-stimulating agent (ESA) responsiveness has been reported to be associated with increased mortality in hemodialysis (HD) patients. ESA requirement to obtain the same hemoglobin (Hb) level is different between HD and peritoneal dialysis (PD) patients. In this study, we investigated the impact of ESA responsiveness on mortality between both HD and PD patients. Prevalent HD and PD patients were selected from the Clinical Research Center registry for end-stage renal disease, a prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 27 publications
3
29
0
2
Order By: Relevance
“…We found a strong association between higher ERI and laboratory evidence of systemic inflammation. Others have reported similar findings [ 5 , 17 ]. None of our patients were iron deficient or had an obvious infection.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We found a strong association between higher ERI and laboratory evidence of systemic inflammation. Others have reported similar findings [ 5 , 17 ]. None of our patients were iron deficient or had an obvious infection.…”
Section: Discussionsupporting
confidence: 78%
“…Another study that was conducted in PD patients reported no influence of RRF on ERI [ 17 ]. A recent, large observational study reported that ERI was higher for patients on HD as compared to those on PD [ 5 ]. It is unclear whether patients included were on stable ESA doses and what the effect RRF may have had.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esse dado é semelhante em vários estudos (BAE et al, 2015;GONÇALVES et al, 2013;OLIVEIRA et al, 2014;SANABRIA et al, 2015). Ao analisarmos a média Ainda Bevilacqua et al (1995) descreveu dados referentes ao tempo de acompanhamento inferior ao deste estudo como também, Oliveira et al (2016) no qual o tempo de acompanhamento foi de 1,5 anos de seguimento.…”
Section: Discussionunclassified